Exploring Hebephrenic Schizophrenia through the Lens of Adlerian Individual Psychology Theory - Muhammad Ryan Maulana; Qurrota A’yuni Fitriana (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Hebephrenic schizophrenia is a subtype of schizophrenia marked by disorganized thinking, emotional disturbance, and impaired social functioning. Beyond its medical aspects, hebephrenic schizophrenia can be explained from a psychological lens through Adler's individual theory. Adler’s theory emphasizes the importance of life meaning, social interest, and responses to feelings of inferiority in shaping one’s personality and behavior, rather than solely focusing on clinical symptoms. This study aims to explore the psychological dynamics of a person with hebephrenic schizophrenia using Adlerian theory as a conceptual lens. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews, direct observations, and reviewing the patient's medical records, involving one patient and one significant other. The findings reveal that the patient experiences intense feelings of inferiority, rooted in a history of neglectful parenting during childhood. This contributed to the development of a maladaptive lifestyle, making emotional expression difficult and prompting the creation of an imaginary world where the patient feels important and accepted. The study highlights how Adlerian concepts can offer deeper insight into the patient’s psychological experience beyond clinical symptoms. These findings suggest the potential of Adlerian-based interventions in supporting individuals with hebephrenic schizophrenia.